Divalent Transition Metal Complexes Derived from Thiocarbohydrazide and Dimedone - Singh, D.P.; Sharma, Chetan; Aneja, K.R. (Asian Journal of Chemistry, 2012)
A new series of macrocyclic metal complexes have been synthesized by the template reaction of thiocarbohydrazide and dimedone resulting into the formation of complexes of the type: [M(C18H28N8S2)X2]; where M = Co(II), Ni(II), Cu(II), Zn(II) and X = Cl–, NO3–, CH3COO–. The synthesized complexes have been characterized by elemental analyses, conductance measurements, magnetic susceptibility measurements and fluorescence, electronic, infrared, 1H NMR and mass spectral studies. The in vitro antibacterial activities of these macrocyclic complexes have also been investigated.